Searchlight Classification Informative Region Mixture Model (SCIM): Identification of Cortical Regions Showing Discriminable BOLD Patterns in Event-Related Auditory fMRI Data - Annika Urbschat; Stefan Uppenkamp; Jörn Anemüller (Frontiers in Neuroscience, 2021)
The investigation of abstract cognitive tasks, e.g., semantic processing of speech, requires the simultaneous use of a carefully selected stimulus design and sensitive tools for the analysis of corresponding neural activity that are comparable across different studies investigating similar research questions. Multi-voxel pattern analysis (MVPA) methods are commonly used in neuroimaging to investigate BOLD responses corresponding to neural activation associated with specific cognitive tasks. Regions of significant activation are identified by a thresholding operation during multivariate pattern analysis, the results of which are susceptible to the applied threshold value. Investigation of analysis approaches that are robust to a large extent with respect to thresholding, is thus an important goal pursued here. The present paper contributes a novel statistical analysis method for fMRI experiments, searchlight classification informative region mixture model (SCIM), that is based on the assumption that the whole brain volume can be subdivided into two groups of voxels: spatial voxel positions around which recorded BOLD activity does convey information about the present stimulus condition and those that do not. A generative statistical model is proposed that assigns a probability of being informative to each position in the brain, based on a combination of a support vector machine searchlight analysis and Gaussian mixture models. Results from an auditory fMRI study investigating cortical regions that are engaged in the semantic processing of speech indicate that the SCIM method identifies physiologically plausible brain regions as informative, similar to those from two standard methods as reference that we compare to, with two important differences. SCIM-identified regions are very robust to the choice of the threshold for significance, i.e., less “noisy,” in contrast to, e.g., the binomial test whose results in the present experiment are highly dependent on the chosen significance threshold or random permutation tests that are additionally bound to very high computational costs. In group analyses, the SCIM method identifies a physiologically plausible pre-frontal region, anterior cingulate sulcus, to be involved in semantic processing that other methods succeed to identify only in single subject analyses.